A rare presentation of pemphigoid gestationis in pregnancy - Singh, Divya; Prasad, Soumya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Pemphigoid gestationis (PG) is a rare autoimmune bullous dermatosis that may arise or worsen during pregnancy due to dynamic immunological and hormonal changes. This report describes a case of a 36-year-old gravida three, para two woman who developed non-pruritic erythematosquamous lesions at six months of gestation, with no prior history of similar complaints. Clinical evaluation and dermatologic consultation supported the diagnosis of PG, and the patient responded well to topical corticosteroid therapy. Her antenatal course remained uncomplicated, and she delivered a healthy infant via elective caesarean section at 39 weeks. Postpartum recovery was favourable, with near-complete resolution of lesions by four months. This case highlights the importance of early recognition, individualized management, and multidisciplinary care in optimizing maternal and foetal outcomes. Regular counselling is essential to address the disease course, associated risks, and the potential for postpartum relapse or recurrence in subsequent pregnancies.